The association between spirituality and religiousness and mental health. Issue 1 (December 2018) - Vitorino, Luciano; Lucchetti, Giancarlo; Leão, Frederico; Vallada, Homero; Peres, Mario
Abstract The present study aims to investigate how different levels of spirituality and religiousness (high spirituality and high religiousness –S/R, high spirituality and low religiousness –S/r, low spirituality and high religiousness s/R and low spirituality and low religiousness – s/r) are associated with quality of life, depressive symptoms, anxiety, optimism and happiness among adults. A cross-sectional study was carried out among 1, 046 Brazilian adults. Concerning the different levels of spirituality and religiousness, 49.2% had s/r, 26.5% S/R, 17.2% S/r and 7.1% s/R. Participants with S/R had better outcomes as compared to those with s/r and those with S/r in WHOQOL Psychological, Social Relationship and Environment, Optimism and happiness. Participants with s/R had better outcomes as compared to those with s/r in WHOQOL Psychological and Social Relationship, Optimism and happiness. Participants with S/r were different from those with s/r, with higher levels of WHOQOL Environment and happiness but also anxiety. The results revealed that, having higher levels of both spirituality and religiousness were more correlated to better outcomes than having just one of them or none of them. Likewise, having higher levels of religiousness in detriment of higher levels of spirituality was also associated with better outcomes in comparison to others.